How developing countries trade, the institutional constraints - Page, Sheila (Routledge, 1994)
"Europe is at a critical stage in its economic development. There seems to be a widespread desire to pursue coherent initiatives which address current issues. However, it is unclear which policies would fit the agenda." "Europe's Economic Challenge analyses the wide-ranging issues in economic strategy and considers future research possibilities. The book considers broad approaches to industrial strategy; looking at policy mix, institutional conditions for a more dynamic market, and the processes of creating a democratic industrial structure. The authors focus on experience in various countries, both in Europe and North America, in different sectors of the economy, and on the implications of European policies for Third World industrialization. The work includes a detailed discussion of the size of the public sector and its relation to the private sector, innovation, R & D, entrepreneurship and inward investment. Europe's Economic Challenge poses some demanding questions and suggestions, discussion and analysis of which provide a valuable contribution to the search for a successful way forward."--Jacket